2022
DOI: 10.1111/ped.15003
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of spectrogram for detecting wheezing in children

Abstract: Background: Auscultation is an easy way to evaluate and diagnose patients with lung conditions but has the shortcoming of being subjective. Using the spectrogram, it is possible to visualize wheezing. We therefore conducted a study to compare the efficacy of diagnosing wheezing by auscultation versus diagnosing wheezing by spectrogram. Methods: This was an investigation of interrater reliability and agreement in which the subject population consisted of children, and the rater population consisted of pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Ferreira-Cardoso and coworkers found a kappa-agreement on any abnormal sound in good-quality recordings of 0.66 26 . Three pediatric pulmonologists identified wheezes with a kappa of 0.76 in 55 good-quality recordings from six patients 27 . In a clinical study of 115 hospitalized patients, similar kappa-agreements as in our study was found for wheezes and fine crackles, but lower values for rhonchi and coarse crackles 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira-Cardoso and coworkers found a kappa-agreement on any abnormal sound in good-quality recordings of 0.66 26 . Three pediatric pulmonologists identified wheezes with a kappa of 0.76 in 55 good-quality recordings from six patients 27 . In a clinical study of 115 hospitalized patients, similar kappa-agreements as in our study was found for wheezes and fine crackles, but lower values for rhonchi and coarse crackles 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Lung sounds have been visualized by spectrograms, which have been published in textbooks, with the vertical axis representing sound pitch and the horizontal axis representing time [19]. In the spectrogram, intermittent rales are represented by short vertical lines and continuous rales are represented by horizontal lines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a case study has been conducted to investigate user preferences regarding wearable or smart device environmental sound presentation technologies [21]. The visualization of auditory information has been investigated in various fields, including the study of physically visualizing the intensity of sound generated by sound sources using a see-through head-mounted display [22], as well as in music, education, consumer electronics, marine science, medicine, and ecosystems [23][24][25][26][27][28]. By visualizing sound, it may be possible to obtain a variety of information that cannot be obtained simply by hearing.…”
Section: Introduction Background and Previous Researchmentioning
confidence: 99%